S-shaped fused azacorannulene dimer: structural and redox properties - Wang, Weifan (2023)
Because of their unique structural and chemical properties, buckybowl molecules have attracted considerable attention in a wide range of scientific disciplines. The importance and utility of buckybowl molecules significantly increases once they acquire larger π-surface area and/or heteroatoms. The fusion of buckybowl molecules has emerged as a new strategy to extend the π-surface of polycyclic aromatic compounds; however, the π-extension of heteroatom-embedded buckybowls by the fusion strategy is still rare. Here we report the synthesis and propeties of a fused azacorannulene dimer bearing a C62N2 core (1a), which can also be regarded as a double aza[5]helicene. Due to the steric repulsion between two azapentabenzocorannulene moieties, this molecule shows a rigid S-shaped structure where the two azacorannulene bowls face in opposite directions. Stepwise chemical oxidation of 1a resulted in the formation of the corresponding radical cation (1a +) and dication (1a2+), providing an important insight into their aromaticity. The fusion of heteroatom-embedded buckybowls provides a powerful way to synthesize π-extended polycyclic aromatic molecules.